The therapeutic potential of short-chain fatty acids enemas in inflammatory bowel diseases: a systematic review - Nina Kaczmarek; Marta Kokot; Aleksandra Makarewicz; Aleksandra Glapa-Nowak; Jan Krzysztof Nowak; Małgorzata Jamka; Jarosław Walkowiak (Polish Pharmaceutical Society, 2020)
It has been suggested that short-chain fatty acid (SCFA) enemas might improve clinical, endoscopic and histological scores in patients with inflammatory bowel disease. However, despite the promising results of in vitro studies, the findings of animal studies and randomised controlled trials are inconclusive. Therefore, this review aimed to assess the efficacy of SCFA enemas in patients with inflammatory bowel diseases. Electronic searches were performed in PubMed, Scopus, Web of Science and Cochrane databases. Original studies were included in this systematic review if they met the following inclusion criteria: 1) types of studies: parallel or crossover randomised controlled trials; 2) language: articles published in English; 3) types of interventions: SCFA enemas; 4) population: studies conducted in subjects with ulcerative colitis or Crohn's disease of either gender and any age and without restrictions based on the ethnicity of study participants, location of study or sample size. The outcomes included the effect of SCFA enemas on disease activity index (DAI), endoscopic and histological scores. In total, four studies enrolling 187 patients with inflammatory bowel diseases were included in this systematic review. Two studies assessed the effect of SCFA enemas on DAI. Four studies evaluated the effect of SCFA therapy on the endoscopic score and the histological score. There were no significant differences between the SCFA groups and the control groups regarding the impact on any analysed parameter. Two studies demonstrated a statistically significant decrease in DAI after the intervention period, both in the SCFA groups and the control groups. Similarly, statistically significant differences between pre- and post-intervention endoscopic scores in the SCFA groups were reported in four studies. However, in three studies, a similar effect was demonstrated in the control groups. Besides, in three studies no effect of SCFA enemas on the histological score was observed. In conclusion, there is no evidence for the effectiveness of SCFA enemas in patients with inflammatory bowel diseases.